How do accountability problems lead to maternal health inequities? A review of qualitative literature from Indian public sector - Mukesh Hamal; Marjolein Dieleman; Vincent De Brouwere; Tjard de Cock Buning (Frontiers Media S.A., 2018)
Abstract Background There are several studies from different geographical settings and levels on maternal health, but none analyzes how accountability problems may contribute to the maternal health outcomes. This study aimed to analyze how accountability problems in public health system lead to maternal deaths and inequities in India. Methods A conceptual framework was developed bringing together accountability process (in terms of standard setting, performance assessment, accountability (or answerability, and enforceability) -an ongoing cyclical feedback process at different levels of health system) and determinants of maternal health to analyze the influence of the process on the determinant leading to maternal health outcomes. A scoping review of qualitative and mixed-methods studies from public health sector in India was conducted. A narrative and interpretive synthesis approach was applied to analyze data. Results An overarching influence of health system-related factors over non-health system-related factors leading to maternal deaths and inequities was observed. A potential link among such factors was identified with gaps in accountability functions at all levels of health system pertaining to policy gaps or conflicting/discriminatory policies and political commitment. A large number of gaps were also observed concerning performance or implementation of existing standards. Inherent to these issues was potentially a lack of proper monitoring and accountability functions. A critical role of power was observed influencing the accountability functions. Conclusion The narrative and interpretive synthesis approach allowed to integrate and reframe the relevant comparable information from the limited empirical studies to identify the hot spots of systemic flaws from an accountability perspective. The framework highlighted problems in health system beyond health service delivery to wider areas such as policy or politics justifying their relevance and importance in such analysis. A crucial message from the study pertains to a need to move away from the traditional concept of viewing accountability as a blame-game approach and a concern of limited frontline health workers towards a constructive and systemic approach.